Climate change mitigation potential of paludiculture in Finland: greenhouse gas emissions of abandoned organic croplands and peat substitution - Myllyviita, Tanja; Grönroos, Juha; Mattila, Tuomas; Lång, Kristiina (Taylor & Francis, 2024)
Introduction: Rewetting is an option to decrease greenhouse gas emissions of drained peatlands. With continued cultivation of wetland plants (paludiculture), it is possible to provide renewable raw materials. In Finland, peat has been used as a growing media and animal bedding. Since peat availability is decreasing, new materials are needed. Methods: The emissions of the paludiculture system were compared to emissions of the current system based on use of peat. We assumed that abandoned organic croplands were under paludicrop cultivation. Paludicrops were used instead of peat as animal bedding material and growing media. The assessment included an analysis of uncertainties related to the key parameters. Results: Paludiculture would generate emissions savings of 352,000 tons of CO2 eq in 2050 compared to the peat use system. The emissions savings are mostly generated by land-use emissions reductions. Emissions of peat decay represent 22% of the emissions of the peat use system, whereas emissions of peat extraction are less significant. Emissions of the paludiculture system are mainly caused by paludicrop cultivation, with 300,000 tons of CO2 eq in 2050. Paludiculture mitigates climate change by increasing biogenic carbon sink: 48,000 tons of CO2 eq in 2050. Discussion: It is highly unlikely that the paludiculture system would generate more emissions than the peat use system. However, peat substitution does not offset emissions of abandoned organic croplands, even under paludicrop cultivation. Therefore, other land-use options, such as afforestation or restoration, could provide more emissions savings even though they do not provide raw materials.
Keywords: greenhouse gas emissions; paludiculture; peat; peatlands